On scaling of the maximum ice pressure on a vertical foundation - Fransson, Lennart; Olofsson, Thomas (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2005)
The nature of ice loads on vertical foundations is discussed based on statistical analysis of field data. Measured loads on segments of the total pressure area were typically Weibull distributed with a maximum of about 4 times the mean values. Scale effect on the maximum effective pressure was evident for uniform level ice when calculated for different contact widths. Maximum pressure on a larger contact width decreased but the mean pressure level remained constant. This confirmed the assumption that some but not all of the governing crushing phenomena were statistically independent. Elasticity of the structure or the ice sheet was assumed to increase the length of the independent crushing zones. Godkänd; 2005; 20070520 (ysko)